Demographic and High-Risk Behaviors associated with HPV and HPV Vaccine Awareness among Persons Aged 15-74 Years in Puerto Rico - Reyes, Juan Carlos; Sánchez-Díaz, Carola T.; Tortolero-Luna, Guillermo; Colón, Hector M.; Ortiz, Ana Patricia (Puerto Rico Health Sciences Journal, 2015)
Objective: Studies of human papillomavirus (HPV) awareness in Puerto Rico (PR) are limited and are of interest given low HPV vaccine uptake in this population. This cross-sectional study aimed to determine factors associated to HPV and HPV vaccine awareness among persons aged 15-74 years living in Puerto Rico. Methods: We analysed data from a sub-sample of 1,476 men and women who participated in a 2008 population-based island-wide household survey and who completed an HPV module. Multivariate logistic regression models were used to examine factors associated with HPV and HPV vaccine awareness. Results: Overall, 37.2% of participants had heard about HPV and 33.4% had heard of the vaccine. Multivariate logistic regression showed that women were more likely to have heard of HPV (OR adjusted: 4.54; 95% CI=3.45, 5.98) or of the HPV vaccine (OR adjusted: 6.15; 95% CI=4.50, 8.40) as compared to men. HPV awareness was also lower among older adults, persons with lower income and with lower educational attainment, those without children and smokers (p<0.05). Conclusion: In 2008, two years after the introduction of the first HPV vaccine in PR and the US, public awareness about HPV infection and the HPV vaccine was lower in Hispanics in PR as compared to other populations. Identified high-risk populations should be targeted in preventive care strategies. Future efforts should increase HPV knowledge and vaccine use in this population in order to maximize the impact of vaccination programs.